2012
DOI: 10.5467/jkess.2012.33.7.637
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Damaging Earthquakes Occurred in Seoul Metropolitan Area for the Last Two Thousand Years

Abstract: Abstract:The Seoul metropolitan area is densely populated with 40 percent of Korean people and quite weak to the seismic hazard. According to the analysis of historical documents, the largest earthquake occurred in this area is MMI VIII-IX acompanying with a large shaking, collapse of stone walls, collapse of houses, and many casualties. Two times of damaging earthquakes occurred in the first century (A.D. 27, 89), and there was a long quiet period of about 1430 years. Another big earthquakes re-occurred three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Previous studies report devastating historical earthquakes in the Korean Peninsula (Kyung, 2012; Park et al., 2020). The historical seismicity displays high similarity with the instrumental seismicity (Hong et al., 2018; Houng & Hong, 2013; Park et al., 2020) (Figure 1c).…”
Section: Data and Geologymentioning
confidence: 97%
See 3 more Smart Citations
“…Previous studies report devastating historical earthquakes in the Korean Peninsula (Kyung, 2012; Park et al., 2020). The historical seismicity displays high similarity with the instrumental seismicity (Hong et al., 2018; Houng & Hong, 2013; Park et al., 2020) (Figure 1c).…”
Section: Data and Geologymentioning
confidence: 97%
“…There is increasing concern regarding possible large earthquakes in the peninsula. There were seismic intensities reaching VII‐IX according to historical seismic damages (Kyung, 2012; K. Lee & Yang, 2006; Park et al., 2020). There were large earthquakes in the Korean Peninsula, including the Seoul metropolitan area (Park et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Located away from any plate boundaries, the Korean peninsula is regarded as a typical region of intraplate seismicity. Recent review on damaging historic earthquakes in SMR revealed the largest potential earthquake in the area is MMI (Modified Mercalli Intensity) VIII-IX with a long recurrence interval of about 1400-1500 years (Kyung, 2012). Large earthquakes in the SMR and Korean peninsula have been rare during modern instrumental earthquake recording that began 1905.…”
Section: Discussionmentioning
confidence: 99%